THE DEVELOPMENT OF AUDIOVISUAL TEACHING MEDIA BASED ON GRAPHIC ORGANIZER TO IMPROVE STUDENTS’ ABILITY IN FINDING THE MAIN IDEA OF A PARAGRAPH - Euis Indah Kesuma Ningsih; Auffah Yumni; Riris Nurkholidah Rambe (JURNAL TARBIYAH, 2021)
This study aims to determine the validity, practicality, and effectiveness of the development of audio-visual teaching media based on Graphic Organizer to improve students’ ability to find the main idea of a paragraph at the fifth grade of MIN 2 in Labuhanbatu Selatan. This study follows the Research and Development (R & D) developed by Borg and Gall and has been modified by Sugiyono. This includes nine steps, namely; Potential and Problems, Gathering Information, Product Design, Design Validation, Design Revision, Product Trial, Revision Product, Trial of Use, and Revision of Final Products. The data were collected from interviews, observation, and questionnaires. There were three instruments used, namely preliminary instruments, product development instruments, and product testing instruments. The data were analyzed using descriptive qualitative and quantitative analysis to describe the results of product development. The findings of this study indicate that 1) the validity of assessment made by the material experts of the product media was found to be 80%. The media expert’s assessment of product media obtained a percentage of 86.6%; 2) In terms of the practicality of the product, the percentage of responses given by small-scale students shows 97.6% and the percentage of responses given by large-scale students is 98.4%. Meanwhile, the results of the questionnaires filled by the teacher is 100%, which is adjusted to the practicality criteria table; 3) the average score for the effectiveness before using the product is 76.87%. Meanwhile, the average score for the effects after using the product is 94.37